Development of Web-Based Instructional Model - . Fadli (International Conference on Education and Language (ICEL), 2013)
Development of web-based instructional model is expected toencourage the involvement of students actively and constructively to the media, so the learning process a fun, creative, and not boring. Developmentof a modelof instructional social networking website that can be used by an individual or several peopleat once (networking /collaboration).An interactive learning materials were developed, so thatstudents can be motivated in learning. Teacher acted as a facilitator in this case to motivate students verbally and non verbally(using webmedia). The work of students in the form of training, evaluation, orquestions and responses will be stored in the program are made,and it will facilitate teachers to recapitulate(correcting) the work ofthese students. Design development of the model is divided intothree parts, namely:1) a conceptual modelas a manifestationof the theory and principles related to web-based learning, 2) a model as a form of procedural stages of the formation of a web-basedlearning sites, 3) physical models to obtainevidencederived from empirical data on the results obtained from the development of web-based learning model.